Atomic scale influences on the tribology of nano to meso-scale systems - Annett, James (Trinity College (Dublin, Ireland). School of Physics, 2015)
It has been known for many years that atomic scale effects can directly influence the tribological behaviour over a wide variety of contact sizes ranging from the nano-scale to macroscale. A newly developed load and depth sensing three dimensional nano-contact system has been used to investigate and experimentally characterise new ways in which atomic scale properties can influence the behaviour of nano to meso-scale contacts in room temperature ambient conditions.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin